A thienyl polymer having a hydrazide structure, a self-healing polypropylene composite material and a preparation method thereof
Patent Information
- Application Number
- CN202611382524.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-13
AI Technical Summary
比如,聚丙烯粒子中的催化剂残留(如齐格勒-纳塔催化剂中的钛、镁、铝等),会在薄膜中形成局部导电点或高场强集中区,在电场作用下易引发提前击穿,更为关键的是,在自愈合过程中,金属杂质会阻碍击穿通道处金属化电极的完全蒸发,导致残留碳化或金属桥接,从而抑制自愈合的有效性,并加速电容量衰减
本发明解决了由于现有聚丙烯复合材料制备的双向拉伸聚丙烯电容膜的金属杂质残留等,而存在的自愈合性差,耐温性和电容量保持率低的问题,通过在聚丙烯复合材料中引入具有酰肼结构的噻吩聚合物,其与聚丙烯的相容性良好且可有效“锁住”聚丙烯复合材料中的金属杂质等组分,可降低这些组分对双向拉伸聚丙烯电容膜的性能的不利影响,从而提高双向拉伸聚丙烯电容膜的自愈合能力,使得双向拉伸聚丙烯电容膜获得改善的耐温性和电容量保持率。
Smart Images

Figure CN122897972A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thiophene polymer technology, and particularly relates to a thiophene polymer with an acylhydrazine structure, a self-healing polypropylene composite material, and a method for preparing the same. Background Technology
[0002] Biaxially oriented polypropylene capacitor films, made from polypropylene composite materials, are widely used in power capacitors, electronic circuits, and new energy fields due to their advantages such as low dielectric loss, high insulation resistance, and good mechanical strength. The self-healing performance of the capacitor film is one of the key indicators for evaluating its reliability: when a local breakdown occurs in the dielectric, the metallized electrodes around the breakdown point can evaporate instantly, isolating the breakdown area from the normal area, thereby restoring the capacitor's insulation performance and preventing overall failure.
[0003] However, in actual production, the self-healing performance of biaxially oriented polypropylene (BOP) capacitor films is poor. Specifically, under high temperature or long-term operating conditions, they exhibit insufficient temperature resistance and are prone to thermal instability. Simultaneously, the capacitance decays rapidly over time, severely shortening the capacitor's lifespan. A systematic analysis of the preparation process and raw materials revealed that the quality and impurities contained in the polypropylene particles, the basic raw material for capacitor films, are the main reasons for the aforementioned deterioration in self-healing performance. These include excessively high levels of metallic impurities, ash, and residual inorganic fillers. For example, catalyst residues in the polypropylene particles (such as titanium, magnesium, and aluminum in Ziegler-Natta catalysts) can form localized conductive points or high-field-strength concentrated areas in the film, easily leading to premature breakdown under the influence of an electric field. More critically, during the self-healing process, metallic impurities hinder the complete evaporation of the metallized electrode at the breakdown channel, resulting in residual carbonization or metal bridging, thereby inhibiting the effectiveness of self-healing and accelerating capacitance decay. For example, trace metal particles (such as iron, copper, calcium, etc.) may be introduced into polypropylene particles during polymerization, granulation and storage. This will form a rigid foreign interface in the film. These interfaces have different coefficients of thermal expansion than the matrix resin, which will cause local stress concentration and microcracks under temperature cycling or high temperature environment, weakening the temperature resistance of the film and reducing the insulation recovery ability after successful self-healing.
[0004] Therefore, how to effectively improve the self-healing ability of biaxially oriented polypropylene capacitor films prepared from polypropylene composites in order to improve their temperature resistance and capacitance retention rate is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] To address the shortcomings of the prior art, this invention provides a thiophene polymer with an acylhydrazine structure, a self-healing polypropylene composite material, and a method for preparing the same. The inventors have discovered that by introducing a thiophene polymer with an acylhydrazine structure into a polypropylene composite material, it is possible to effectively "lock in" residual metal impurities in the polypropylene material, reducing the adverse effects of these components on the performance of the biaxially oriented polypropylene capacitor film prepared from the polypropylene composite material. This improves the self-healing ability of the biaxially oriented polypropylene capacitor film, resulting in improved temperature resistance and capacitance retention.
[0006] The first objective of this invention is to provide a thiophene polymer having an acylhydrazine structure, comprising a polythiophene backbone segment and a structural unit represented by formula (I): Equation (Ⅰ).
[0007] In this invention, the thiophene polymer with the acylhydrazine structure exhibits good compatibility with polypropylene, enabling it to be uniformly and stably dispersed in the polypropylene composite material / capacitor film, thus maintaining its mechanical and electrical properties. Furthermore, its acylhydrazine structure has a chelating effect, potentially "locking in" residual metal impurities in the polypropylene composite material through chelation or other physical bonding, thereby improving the self-healing ability, temperature resistance, and capacitance retention of the capacitor film prepared from the polypropylene composite material. Moreover, the acylhydrazine structure in the structural unit shown in formula (I) has symmetrical structures on both sides, and the steric hindrance effect is relatively small, which is beneficial for the acylhydrazine structure to exert its chelating and physical bonding effects. Additionally, it is understood that the structural unit shown in formula (I) is connected to the polythiophene main chain segment by at least one single bond; that is, one or both ends of the structural unit shown in formula (I) can be connected to the polythiophene main chain segment by a single bond.
[0008] In some embodiments of the present invention, the raw materials for preparing the above-mentioned thiophene polymer having an acylhydrazine structure include: a thiophene polymer containing a carboxyl group and a compound represented by formula (II); Formula (II).
[0009] In some embodiments of the present invention, the number-average molecular weight of the thiophene polymer containing the carboxyl group is 5-40 kDa, and the molecular weight distribution is 1.2-3.5.
[0010] In some embodiments of the present invention, the structure of the thiophene polymer containing the carboxyl group is shown in formula (Ⅲ): Formula (III); wherein, in Formula (III), R1 represents an alkyl chain with 6 to 18 carbon atoms, R2 represents a direct bond or an alkylene chain with 1 to 6 carbon atoms, and x is 0.5 to 0.95. Preferably, R1 represents an alkyl chain with 6 to 12 carbon atoms, or even 6 carbon atoms, or more preferably a straight alkyl chain; R2 represents a direct bond, that is, the carboxyl structure is directly attached to the thiophene structure. In addition, in specific embodiments, x can be 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, or 0.9.
[0011] Another object of the present invention is to provide a method for preparing the above-mentioned thiophene polymer having an acylhydrazine structure, comprising the following steps: Step SS1. Synthesize thiophene polymers containing carboxyl groups; Step SS2. After dissolving the thiophene polymer containing the carboxyl structure obtained in SS1, add an excess of the compound shown in formula (II) and a catalytic amount of bismuth isooctanoate, and react at 80~120℃ for 6~24h, continuously removing water from the system, and then perform post-treatment to obtain the thiophene polymer with the acylhydrazine structure.
[0012] In some embodiments of the present invention, step SS1 includes: reacting a compound with structure (Ⅳ) and a compound with structure (Ⅴ) at 80~120°C for 12~36h under the conditions of a catalyst and a reaction aid, followed by post-treatment to obtain the thiophene polymer containing a carboxyl group structure. Formula (Ⅳ), where R1 represents an alkyl chain with 6 to 18 carbon atoms; Formula (V), where R2 represents a direct bond or an alkylene chain with 1 to 6 carbon atoms.
[0013] In some embodiments of the present invention, the molar ratio of the compound with structure (Ⅳ) to the compound with structure (Ⅴ) is 0.5~0.95:0.05~0.5. In specific embodiments of the present invention, the former may be 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85 or 0.9, and the latter may be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4 or 0.45.
[0014] Another object of the present invention is to provide a self-healing polypropylene composite material, the raw materials for which include: (a) polypropylene, and (b) the thiophene polymer having an acylhydrazine structure as described above or the thiophene polymer having an acylhydrazine structure obtained by the above preparation method.
[0015] In some embodiments of the present invention, the thiophene polymer with an acylhydrazine structure accounts for 0.05-2% of the raw materials used in the preparation, by mass percentage. For example, it can be 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, or 1.9%. By preferably selecting a mass percentage of the thiophene polymer with an acylhydrazine structure within the above range, the present invention is beneficial for maintaining the mechanical properties, electrical properties, and self-healing properties of the polypropylene composite material / capacitor film itself.
[0016] In some embodiments of the present invention, the polypropylene accounts for 90% to 99.95% of the raw materials by mass percentage, for example, 92%, 94%, 96%, 98%, 99% or 99.5%.
[0017] Another object of the present invention is to provide a method for preparing the above-mentioned composite material, comprising the following steps: mixing raw materials including (a) polypropylene and (b) a thiophene polymer having an acylhydrazine structure, and melt-extruding to obtain the self-healing polypropylene composite material.
[0018] In some embodiments of the present invention, the above preparation method specifically includes the following steps: after obtaining the self-healing masterbatch containing the thiophene polymer with the acylhydrazine structure described in (b) by solution method, the remaining preparation raw materials are mixed with the self-healing masterbatch and melt-extruded to obtain the self-healing polypropylene composite material.
[0019] Furthermore, the solution method described above refers to dissolving polypropylene and (b) thiophene polymer with an acylhydrazine structure in a good solvent (heating may be necessary for dissolution), followed by adding a poor solvent to precipitate a solid powder. The melt index of the polypropylene forming the self-healing masterbatch is 2.5 to 3.5. By selecting polypropylene within this melt index range, it is advantageous to process the thiophene polymer with the acylhydrazine structure into the self-healing masterbatch. Moreover, in this invention, the melt index of (a) polypropylene can be 1.0 to 5.0, preferably within the melt index range of 2.5 to 3.5 used in the self-healing masterbatch, and the melt index is obtained under conditions of 2.16 kg and 230°C.
[0020] Compared with the prior art, the present invention has the following beneficial effects: This invention addresses the problems of poor self-healing ability, low temperature resistance, and low capacitance retention in biaxially oriented polypropylene capacitor films prepared from existing polypropylene composite materials due to residual metal impurities. By introducing a thiophene polymer with an acylhydrazine structure into the polypropylene composite material, which has good compatibility with polypropylene and can effectively "lock in" metal impurities and other components in the polypropylene composite material, the adverse effects of these components on the performance of the biaxially oriented polypropylene capacitor film can be reduced, thereby improving the self-healing ability of the biaxially oriented polypropylene capacitor film and achieving improved temperature resistance and capacitance retention. Attached Figure Description
[0021] Figure 1 The nuclear magnetic resonance hydrogen spectrum of the thiophene polymer with an acylhydrazine structure obtained in Example 1 of this invention. Detailed Implementation
[0022] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this invention.
[0023] The raw materials used in the specific embodiments of this invention are all commercially available.
[0024] PP: PPH-FC03 Palladium catalyst C:
[0025] Example 1 This embodiment provides a thiophene polymer P1 with an acylhydrazine structure, and its specific preparation method is as follows: SS1. Under a nitrogen atmosphere, 2-bromo-3-thiophene carboxylic acid, 2-bromo-3-hexylthiophene (molar ratio 1:1), potassium carbonate (150 mol% relative to the monomers), palladium catalyst C (0.25 mmol% relative to the monomers), and terpentine (30 mol% relative to the monomers) were dispersed / dissolved in dimethylacetamide and reacted at 100 °C for 24 h. The thiophene polymer containing a carboxyl group was then precipitated in methanol. SS2. Under a nitrogen atmosphere, the thiophene polymer containing a carboxyl group obtained in SS1 was dissolved in toluene, and then an excess of the compound shown in formula (II) (twice the mass of the thiophene polymer containing a carboxyl group) and a catalytic amount of bismuth isooctanoate were added. The reaction was carried out at 100°C for 12 h, and water in the system was continuously removed. After filtration, redissolving in toluene and precipitating with methanol, the thiophene polymer P1 with an acylhydrazine structure was obtained.
[0026] The proton NMR spectrum of the thiophene polymer with the acylhydrazine structure is as follows: Figure 1 As shown, the chemical shift of 5.60 ppm is the peak of hydroxyl (-OH)H and 8.11 ppm is the peak of imino (-NH-NH-)H, indicating that the thiophene polymer P1 has the structural unit shown in formula (Ⅰ) and at least part of the structural unit is connected to the polythiophene main chain segment through one end.
[0027] Example 2 This embodiment provides a thiophene polymer P2 with an acylhydrazine structure, which differs from Preparation Example 1 only in that the molar ratio of 2-bromo-3-thiophenecarboxylic acid and 2-bromo-3-hexylthiophene in step SS1 is adjusted to 3:7, while the rest remains the same as Preparation Example 1.
[0028] Example 3 This embodiment provides a thiophene polymer P3 with an acylhydrazine structure, which differs from Preparation Example 1 only in that the molar ratio of 2-bromo-3-thiophenecarboxylic acid and 2-bromo-3-hexylthiophene in step SS1 is adjusted to 1:9, while the rest remains the same as Preparation Example 1.
[0029] Example 4 This embodiment 1 provides a self-healing polypropylene composite material, which, by mass percentage, comprises 0.05% of the thiophene polymer P1 with an acylhydrazine structure obtained in Example 1 and 99.95% of PP. The specific preparation steps are as follows: S1. The thiophene polymer with an acylhydrazine structure obtained in Example 1 and PP were mixed at a mass ratio of 1:99 and added to a reaction vessel. Then, p-xylene was added to the system, and the mixture was heated and stirred at about 125°C to form a homogeneous solution. The stirring was continued until the system was completely clear. Then, the hot solution was slowly added dropwise to excess ethanol under stirring to cause the mixture to precipitate and form a solid powder precipitate. The precipitate was separated by vacuum filtration and washed twice with ethanol. The wet powder obtained by filtration was placed in a vacuum oven at 50°C and dried for 24 hours to reduce the solvent residue to a negligible level, thus obtaining the self-healing masterbatch. Next, the self-healing masterbatch was mixed with the remaining PP and melt-extruded at a temperature controlled within the range of 235~265°C to obtain the self-healing polypropylene composite material.
[0030] Examples 5-9 The above embodiments provide a self-healing polypropylene composite material, which differs from Example 4 only in that the type / amount of the thiophene polymer with the hydrazide structure is different, as shown in Table 1, while the rest is consistent with Example 4.
[0031] Comparative Example 1 This comparative example provides a polypropylene composite material that differs from Example 1 only in that it does not use a thiophene polymer with an acylhydrazine structure, but instead uses a thiophene polymer with a carboxyl group structure (referred to as P10) obtained in step SS1 of Example 1, as shown in Table 1. Otherwise, it remains the same as Example 4.
[0032] Table 1: Raw material composition of different polypropylene composites
[0033] Performance testing: 1. The aluminum content and ash content of the polypropylene composite materials obtained in Examples 4-9 and Comparative Example 1, as well as the elongation at break of the cast sheets of the polypropylene composite materials under the condition of tensile speed of 50 mm / min, were tested. The results are shown in Table 2. 2. The polypropylene composite materials obtained in Examples 4-9 and Comparative Example 1 were processed into plasticized melts, extruded, biaxially stretched (the stretching ratios in the MD and TD directions were 6 and 8 respectively), and cured to obtain biaxially stretched polypropylene capacitor films.
[0034] On the one hand, the breakdown strength of the obtained biaxially oriented polypropylene capacitor film at 125°C was tested, and the results are shown in Table 2. On the other hand, the capacitance retention rate of the film capacitor formed from the biaxially oriented polypropylene capacitor film was tested: the biaxially oriented polypropylene capacitor film was coated, wound, statically pressed, heat-set, sputter-coated, and encapsulated to obtain the film capacitor; the two electrodes of the film capacitor were connected to a power source to test the initial capacitance value; then the film capacitor was placed in a 125°C constant temperature oven with a DC voltage of 900V applied, and the capacitance value was measured after running in the oven for different hours, with the final capacitance value measured after 500 hours. Three groups of experiments were conducted, and the capacitance change rate was calculated by averaging. A capacitance change exceeding -5.0% indicated that the capacitor had failed. The results are shown in Table 3.
[0035] Table 2: Performance of Polypropylene Composite Materials and Biaxially oriented Polypropylene Capacitor Films
[0036] Table 3: Performance of Thin Film Capacitors
[0037] As shown in Tables 2-3, although the polypropylene composites of Examples 4-9 and Comparative Example 1 have considerable aluminum content and ash content, the biaxially oriented polypropylene capacitor films prepared from the polypropylene composites of Examples 4-9, which incorporate a thiophene polymer with an acylhydrazine structure, exhibit improved breakdown strength at high temperatures. Furthermore, the film capacitors prepared from these biaxially oriented polypropylene capacitor films demonstrate good capacitance retention at high temperatures. This indicates that the thiophene polymer with an acylhydrazine structure can effectively "lock in" metallic impurities in the polypropylene composites, reducing the adverse effects of these components on the performance of the biaxially oriented polypropylene capacitor films. This improves the self-healing ability of the biaxially oriented polypropylene capacitor films, resulting in improved temperature resistance and capacitance retention.
[0038] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that after reading this application specification, they can still modify or make equivalent substitutions to the specific implementation of the present invention, but these modifications or changes do not depart from the protection scope of the pending claims of the present invention.
Claims
1. A thiophene polymer having an acylhydrazine structure, characterized in that, Contains a polythiophene main chain segment and the structural unit shown in formula (Ⅰ): Equation (Ⅰ).
2. The thiophene polymer having an acylhydrazine structure according to claim 1, characterized in that, The raw materials for preparation include: a thiophene polymer containing a carboxyl group and a compound represented by formula (II); Formula (II).
3. The thiophene polymer having an acylhydrazine structure according to claim 2, characterized in that, The number-average molecular weight of the thiophene polymer containing a carboxyl group is 5-40 kDa, and the molecular weight distribution is 1.2-3.
5. And / or, the structure of the thiophene polymer containing the carboxyl group is as shown in formula (III): Formula (Ⅲ); wherein, in Formula (Ⅲ), R1 represents an alkyl chain with 6 to 18 carbon atoms, R2 represents a direct bond or an alkylene chain with 1 to 6 carbon atoms, and x is 0.5 to 0.
95.
4. The method for preparing the thiophene polymer having an acylhydrazine structure according to any one of claims 1 to 3, characterized in that, Includes the following steps: Step SS1. Synthesize thiophene polymers containing carboxyl groups; Step SS2. After dissolving the thiophene polymer containing the carboxyl structure obtained in SS1, add an excess of the compound shown in formula (II) and a catalytic amount of bismuth isooctanoate, and react at 80~120℃ for 6~24h, continuously removing water from the system, and then perform post-treatment to obtain the thiophene polymer with the acylhydrazine structure.
5. The preparation method according to claim 4, characterized in that, Step SS1 includes: reacting a compound with the structure of formula (Ⅳ) and a compound with the structure of formula (Ⅴ) at 80~120℃ for 12~36h under the conditions of a catalyst and a reaction aid, followed by post-treatment to obtain the thiophene polymer containing the carboxyl group structure; Formula (Ⅳ), where R1 represents an alkyl chain with 6 to 18 carbon atoms; Formula (V), where R2 represents a direct bond or an alkylene chain with 1 to 6 carbon atoms.
6. The preparation method according to claim 5, characterized in that, The molar ratio of the compound with structure (Ⅳ) to the compound with structure (Ⅴ) is 0.5~0.95:0.05~0.
5.
7. A self-healing polypropylene composite material, characterized in that, The raw materials for preparation include: (a) polypropylene, and (b) the thiophene polymer having an acylhydrazine structure as described in any one of claims 1 to 3 or the thiophene polymer having an acylhydrazine structure obtained by the preparation method described in any one of claims 4 to 6; In this material, by mass percentage, the polypropylene accounts for 90% to 99.95% of the raw materials, and the thiophene polymer with an acylhydrazine structure accounts for 0.05% to 2% of the raw materials.
8. The method for preparing the composite material according to claim 7, characterized in that, Includes the following steps: The raw materials comprising (a) polypropylene and (b) thiophene polymer having an acylhydrazine structure are mixed and melt-extruded to obtain the self-healing polypropylene composite material.
9. The preparation method according to claim 8, characterized in that, The process includes the following steps: after preparing a self-healing masterbatch comprising the thiophene polymer having the acylhydrazine structure described in (b) by a solution method, the remaining raw materials are mixed with the self-healing masterbatch and melt-extruded to obtain the self-healing polypropylene composite material.